Pelaksanaan Hadhānah di Panti Asuhan Budi Mulya, Sukarame Bandar Lampung - Bunyamin, Mahmudin (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2017)
This articel discusses the process of hadhānah at Budi Mulya orphanage, Sukarame Bandar Lampung. This research indicates that this orphanage has helped to provide stewardship and child care. They take over the parenting attitude of the child, provides all the basic needs of children: food, clothing, and boards. They also prepare formal and non-formal education and equipped them with knowledge and practice of daily worship as their provision in living the world and the hereafter. The factors that motivate caregivers to take care of the orphans are sincere devotion, community support and good infrastructure. But, they obstacle factors that are children from different backgrounds, the implementation of pesantren model not working properly, unprofessional caretakers, and unoptimal of management structure.